SELEKSI KHAMIR YANG BERBASIS SELENIUM SEBAGAI SUMBER BAHAN BIOAKTIF DAN UJI MODULASI APOPTOSIS SELULER SACCHAROMYCES CEREVISIAE - Titin Yulinery; W. R. Handayani; Novik Nurhidayat (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
The selection of yeast from volcanic soil as bioactive source based on selenium and apoptosis modulation of Saccharomyces cerevisiae have been done. Isolation of yeast used the dilution method. Furthermore, the isolates were selected for resistance and accumulation test of selenium, catalyze test, resistance to high temperature and test of toxicity to garlic. The Inhibition activity was detected by using paper disc method. The result showed that 11 isolates from Kerinci and 4 isolates from Rinjani had been determined. 10 isolates were resistant to SeO2 toxicity, could accumulate Se, and had the activity of catalyze. Isolates 15 and 394.1 were sensitive to garlic toxicity, could inhibit 3.71 cm and 4.16 cm, respectively. All the isolates collected were mesophylic, and could grow at the temperature 28–30 °C. The highest Se concentration of the isolates was 0.92 ppm and 0.78 ppm, which produced by isolate 53 and 15 respectively. Isolate 15 were lower than isolate 53 in apoptosis modulation yeast LIPIMC strain and yeast BJ 3505 strain (10.54% and 14.24%, respectively). The highest frequent of petite was BJ 3505 strain.